ISLAMIC IDENTITY IN THE CONTEXT OF HISTORY AND ITS PROSPECTS: RELIGIOUS AND POLITICAL ASPECTS - TURGANBAYEVA, Zhanara; SEITAKHMETOVA, Nataliya; BEKTENOVA, Madina; ZHANDOSSOVA, Sholpan (CENTRAL ASIA AND THE CAUCASUS, 2019)
The article reveals the fundamental aspects of the emergence and development of discourse on Islamic identity as part of the national identity model in Kazakhstan from a historical perspective. It explores the role and place of Islam and its related identity during the Soviet Union era and identifies the conditions under which the significance of Islam and the identity it fosters may evolve in Kazakhstan.The article emphasizes the importance of the global shift in discussions about Islamic identity, moving from an Orientalist perception of the Islamic world to viewing it as an equal actor and entity in constructing human identity.